2018
DOI: 10.2135/cropsci2018.01.0067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Nitrogen Forms on Hormone Metabolism in Potential Storage Roots and Storage Root Number of Sweetpotato

Abstract: In this study, we investigated the effects of two N forms on sweetpotato [Ipomoea batatas (L.) Lam.] root growth and development, zeatin riboside (ZR) and indole‐3‐acetic acid (IAA) concentrations in potential storage roots, and storage root number per plant. During the period 2015 to 2016, field experiments were performed using the sweetpotato cultivars ‘Shangshu 19’ and ‘Jixu 23’, which involved the following three treatments: no application of N fertilizer, application of 60 kg N hm−2 ammonium N, and applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Similar results were observed in a study in which A. lipoferum provided yield gains and protein content in sweet potato roots, even under conditions of reduced use of nitrogen fertilizer (Pérez-Pazos & Sánchez-López, 2018;Sánchez-López et al, 2019). The authors related, among other factors already mentioned, to the improvement of soil quality in the rhizosphere region of this species, allowing greater absorption of nutrients (Subair, 2015;Si et al, 2018).…”
Section: Roots and Tuberssupporting
confidence: 77%
“…Similar results were observed in a study in which A. lipoferum provided yield gains and protein content in sweet potato roots, even under conditions of reduced use of nitrogen fertilizer (Pérez-Pazos & Sánchez-López, 2018;Sánchez-López et al, 2019). The authors related, among other factors already mentioned, to the improvement of soil quality in the rhizosphere region of this species, allowing greater absorption of nutrients (Subair, 2015;Si et al, 2018).…”
Section: Roots and Tuberssupporting
confidence: 77%
“…De igual forma, Pérez-Pazos y Sánchez-López (2017) reportaron la capacidad de estas cepas bacterianas de producir AIA y solubilización de fósforo, medida como la disponibilidad de ortofosfatos, en este caso, la bacteria A. chroococcum IBCR19 presentó una producción de AIA de 49,72 µg.ml -1 y 9,36 ppm de ortofosfatos disponibles, por su parte, la cepa de A. lipoferum IBSC7 se reportó con una producción de AIA de 7,41 µg.ml -1 y de ortofosfatos disponibles 7,14 ppm; lo que indicó que el A. chroococcum IBCR19 y el A. lipoferum IBSC7, tuvieron variadas actividades como PGPRs y sus resultados las perfilaron como bioestimulantes capaces de generar un incremento en el cultivo de batata. Varios estudios indican que el AIA producido por bacterias como PGPRs, puede aumentar el número de raíces laterales y el tamaño del sistema radicular, aumentando así la captación de agua y nutrientes del suelo (Subair, 2015;Si et al, 2018).…”
Section: Discussionunclassified
“…Wagner and Beck (1993) reported that the type and content of cytokinins varied across different plant organs, and that the response of the cytokinins to changes in N levels also differed. While changes in N levels did not affect the total cytokinin content in nettle stems in the study of Wagner and Beck (1993), ammonium N reduced trans-zeatin riboside content in sweet potato storage roots (Si et al 2018). Yong et al (2000) reported that N treatment increased the cytokinin content in the aboveground parts of cotton, especially in the leaves.…”
Section: Introductionmentioning
confidence: 74%
“…Similarly, Sakakibara (2006) also reported that N increased the biosynthesis of endogenous cytokinins in plants, and in uenced the transport of cytokinins from roots to aboveground parts, thus affecting the content and distribution patterns of cytokinins in different organs of plants (Rahayu 2005;Takei et al 2001). At present, reports on the effect of soil-available N on the content of endogenous cytokinins, and other endogenous hormones, such as gibberellin (GA), indole acetic acid (IAA), and abscisic acid (ABA) in different organs of plants are con icting (Liu et al 2011;Si et al 2018;Wang et al 2009). Similarly, the result of studies on the effect endogenous hormones on the allometric growth of plant organs differ considerably.…”
Section: Introductionmentioning
confidence: 99%